Utilizing the VITAL-5G platform to advance 5G standalone integration with vertical industries - Vincent Charpentier; Giada Landi; Eleni Giannopoulou; Juan Brenes; Ronan Frizzell; Marius Iordache; Cristian Patachia; Panagiotis Demestichas; Gabriele Baldoni; Andrea Caruso; Christian Grasso; Giovanni Schembra; et al. (EURASIP Journal on Wireless Communications and Networking)
Abstract The advent of advanced mobile communication systems like 5G and beyond holds promise for vertical sectors, particularly in transport & logistics (T&L), by enhancing network performance and ensuring high levels of quality of service (QoS), crucial for automating and optimizing T&L processes. However, assessing the impact of 5G requires investments in network infrastructure, posing time, and return on investment uncertainties. To address this, the European project VITAL-5G offers an open, virtualized, and flexible experimentation platform that provides 3rd party vertical stakeholders the opportunity to test and validate 5G-enabled services under realistic conditions. This paper explores the VITAL-5G platform’s capabilities, detailing the infrastructure that supports 5G standalone (SA) testing across multiple trial sites, including port and logistics environments. We highlight a subset of performed activities and experimentation campaigns, technical and operational challenges faced by 3rd party experimenters, and the potential business opportunities that emerge from 5G-enhanced services in the T&L sector. Finally, we present insights into future developments and opportunities for extending these capabilities to other vertical sectors.